2007
DOI: 10.1007/s11255-006-9148-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the total volume, transitional zone volume of the prostate, transitional prostate zone index and lower urinary tract symptoms (LUTS)

Abstract: A low correlation was found between the score lower urinary tract symptoms assessed by IPSS and the different volumes of the prostate gland (TV, TZV) and prostate TZI, and, on the other hand, an inverse correlation between the intensity of urinary symptoms and QoL, supporting the idea of multifactorial aspects related to the genesis of urinary symptoms in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…A few studies have shown a positive and statistically significant correlation. [23][24][25] Wang et al 26 reported a correlation coefficient of 0.27 between the prostate volume and the IPSS in a Chinese survey, which is similar to the correlation found in this study. Conversely, no correlation was found between TPV, TZV and the prostate symptoms score evaluated by the IPSS in a study developed by Kaplan et al 27 The discrepancy is that these studies are likely the result of different study populations and methods.…”
Section: Discussionsupporting
confidence: 86%
“…A few studies have shown a positive and statistically significant correlation. [23][24][25] Wang et al 26 reported a correlation coefficient of 0.27 between the prostate volume and the IPSS in a Chinese survey, which is similar to the correlation found in this study. Conversely, no correlation was found between TPV, TZV and the prostate symptoms score evaluated by the IPSS in a study developed by Kaplan et al 27 The discrepancy is that these studies are likely the result of different study populations and methods.…”
Section: Discussionsupporting
confidence: 86%
“…TZI (TZV/TPV) is a parameter that correlates significantly with evaluated parameters of BPH and may serve as a useful proxy for evaluating worsening obstruction. Several studies report that the TZI correlates not only with subjective voiding symptoms of patients but also with objective parameters such as Qmax [20][22]. In our study, IPSS correlated poorly with TZV and TZI, and there was no relationship in the multivariate regression test.…”
Section: Discussioncontrasting
confidence: 57%
“…Although prostate size may not correlate well with the severity of LUTS [12], it is an important predicting factor for the development of AUR in patients with symptomatic BPH and for the long-term outcome of patients who developed AUR. Roehrborn et al reported that for patients who suffer symptomatic BPH, prostate volume and serum PSA level were predictors of the risk of AUR and the need for BPH-related surgery in these patients [13,14].…”
Section: Discussionmentioning
confidence: 99%